Community Empowerment Strategy in Tourism Village Development : Study on Batu Majang Village, Long Bagun District, Mahakam Ulu Regency - Dionisius Jalung; Sri Kamariyah; Ika Devy Pramudiana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This study aims to describe and analyze: Community Empowerment Strategies in Batu Majang, Long Bagun District, Mahakam Hulu Regency, East Kalimantan and Inhibiting and Supporting Factors Affecting Empowerment in Tourism Village Development. The research is qualitative descriptive analysis The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, testing alternative interpretations dan forming and/or refining generalizable theory from case study. The results of the study show that the Community Empowerment Strategy in the Development of Tourism Villages in Batu Majang which is carried out includes: Planning is carried out through community proposals which are then mapped to potential based on ususlan. Implementation of Community Empowerment in Tourism Village Development by involving all elements of Village Muspides, Tourism Awareness Groups and all communities, Providing guidance to the community in a sustainable manner by collaborating with the tourism office, increasing the productive economy. Evaluation or Monitoring of Community Empowerment in Tourism Village Development through a village-level musayawarah forum which is delivered in a village deliberative forum every 3 months. Factors that inhibit community empowerment in the development of Tourism Villages include limited resources, both budget and human resources, traditional community behavior, and limited land. The supporting factors encountered are the support of some people and the existence of promotional media that can support the existence of tourist villages.